Po poteh oblasti in boja - Ploštajner, Klemen (Družboslovne razprave, 2014)
The aim of the article is to point out the problems confronting the fight to change the world through fighting for power. Deriving from the thesis that the means equal the goals and that the specific forms of oppression are inscribed into the mechanisms of taking the state, it is necessary to broaden the existing critique of the relations of power by including the critique of the state. The article seeks to show that all mechanisms which tear power and political organisation out of the community carry within themselves the seeds of their own corruption, of alienation and authoritarianism. Our analysis is mostly based on cases from Latin America where tensions between social movements and the state are most severe.
Keywords: Družbena gibanja; Social movements; state; State, The; Država; Political strategy; Politična strategija; Political power; Politična moč; Latin America; Latinska Amerika